Pyroptosis and Its Role in Autoimmune Disease: A Potential Therapeutic Target - You, Ruixuan; He, Xinglan; Zeng, Zhuotong; Zhan, Yi; Xiao, Yangfan; Xiao, Rong (Frontiers in Immunology, 2022)
Autoimmune diseases are a group of heterogeneous diseases with diverse clinical manifestations that can be divided into systemic and organ-specific. The common etiology of autoimmune diseases is the destruction of immune tolerance and the production of autoantibodies, which attack specific tissues and/or organs in the body. The pathogenesis of autoimmune diseases is complicated, and genetic, environmental, infectious, and even psychological factors work together to cause aberrant innate and adaptive immune responses. Although the exact mechanisms are unclear, recently, excessive exacerbation of pyroptosis, as a bond between innate and adaptive immunity, has been proven to play a crucial role in the development of autoimmune disease. Pyroptosis is characterized by pore formation on cell membranes, as well as cell rupture and the excretion of intracellular contents and pro-inflammatory cytokines, such as IL-1β and IL-18. This overactive inflammatory programmed cell death disrupts immune system homeostasis and promotes autoimmunity. This review examines the molecular structure of classical inflammasomes, including NLRP3, AIM2, and P2X7-NLRP3, as the switches of pyroptosis, and their molecular regulation mechanisms. The sophisticated pyroptosis pathways, including the canonical caspase-1-mediated pathway, the noncanonical caspase-4/5/11-mediated pathway, the emerging caspase-3-mediated pathway, and the caspase-independent pathway, are also described. We highlight the recent advances in pyroptosis in autoimmune diseases, such as systemic lupus erythematosus, rheumatoid arthritis, inflammatory bowel disease, Sjögren’s syndrome and dermatomyositis, and attempt to identify its potential advantages as a therapeutic target or prognostic marker in these diseases.